2018
DOI: 10.1111/cei.13185
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells cross-talk with tumour antigen-specific CD8+ T cells, Vγ9γδT cells and Vα24NKT cells in patients with glioblastoma multiforme and in healthy donors

Abstract: SummaryThe finding that dendritic cells (DCs) orchestrate innate and adaptive immune responses has stimulated research on harnessing DCs for developing more effective vaccines for DC therapy. The expression of cytomegalovirus (CMV) antigens in glioblastoma multiforme (GBM) presents a unique opportunity to target these viral proteins for tumour immunotherapy. Here, we demonstrate that Vγ9γδT cells, innate immune cells activated by zoledronate (Z) and Vα24 natural killer (Vα24NK) cells, innate/adaptive immune ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…This is in stark contrast to the effects of ZOL on PD-1 expression. ZOL downregulates PD-1 expression on Tregs, which both reduces iTreg conversion and reduces the ability of Tregs to functionally supress T effector cells in the tumour microenvironment [100] . Furthermore, ZOL was shown to inhibit the proliferation and migratory capacity of Treg cells which would reduce their capacity to infiltrate the tumour microenvironment.…”
Section: Evidence From Pre-clinical Studiesmentioning
confidence: 99%
“…This is in stark contrast to the effects of ZOL on PD-1 expression. ZOL downregulates PD-1 expression on Tregs, which both reduces iTreg conversion and reduces the ability of Tregs to functionally supress T effector cells in the tumour microenvironment [100] . Furthermore, ZOL was shown to inhibit the proliferation and migratory capacity of Treg cells which would reduce their capacity to infiltrate the tumour microenvironment.…”
Section: Evidence From Pre-clinical Studiesmentioning
confidence: 99%
“…This suggests that a high-risk score may be associated with a secondary elevation of CD4 T cells, dendritic cells and macrophages, as well as a secondary reduction of CD8 T cells. Previous studies have indicated that CD8 T cells and dendritic cells have a positive role in the development of a normal body ( 40-44 ). This may indicate that an increase in the risk score may cause a secondary decrease in CD8 T cells, thereby promoting tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Liu et al conclude that the future of glioblastoma treatments lies in a multifaceted immune response (129). Eiraku et al had a similar conclusion that combinations of DCV and CAR-T cells with ICI may provide a better outcome (53).…”
Section: Conclusion/future Directionsmentioning
confidence: 95%